Unlocking the potential of Earned Value management in construction: A Comparative Study - Elsaid, Mohamed (AUC Knowledge Fountain, 2023)
The implementation of earned value management (EVM) in the construction industry faces challenges when it comes to application, accuracy, and interpretability of results, with potential enhancements yet to be realized. In light of technological advancements, there is an opportunity to develop a controlled EVM approach for improved project management. The goal of this research is to enhance the application and accuracy of earned value techniques in Egyptian construction projects through a comprehensive evaluation of Earned Duration, Earned Schedule, and Planned Value methods. The key challenge that is addressed in this research lies in selecting an optimal technique considering the variations in accuracy based on project type and duration. A comprehensive comparison of three earned value techniques the Earned Duration method, Earned Schedule method, and Planned Value method was conducted across 30 diverse construction projects in Egypt. Encompassing commercial, educational, industrial, renovation, and residential sectors from January 15, 2015, to December 30, 2023, the study evaluates the accuracy of these techniques in predicting project completion dates. The research reveals that project type and duration significantly influence the choice of the most accurate earned value technique. In renovation and residential projects the most accurate is the Earned Schedule method, while industrial, commercial, and educational projects lean towards the Earned Duration method. The inconsistency prompts the need for a systematic approach tailored to specific project characteristics. Practical guidelines for selecting the most efficient technique based on project duration percentages are introduced, aiding project managers in informed decision-making for accurate project forecasting. However, the interplay of performance factors, including SPI and SCI, still requires a nuanced understanding. The research emphasizes the challenge of reconciling the overall effectiveness of the Earned Duration method with nuanced performance variations under different factors and project types. In conclusion, this research contributes a comprehensive and applicable framework to assist project managers in selecting the most efficient earned value technique for precise project forecasting in the unique context of Egyptian construction projects.